2020
DOI: 10.1093/europace/euaa306
|View full text |Cite
|
Sign up to set email alerts
|

Long-term performance and risk factors analysis after permanent His-bundle pacing and atrioventricular node ablation in patients with atrial fibrillation and heart failure

Abstract: Aims His-bundle pacing (HBP) combined with atrioventricular node (AVN) ablation has been demonstrated to be effective in patients with atrial fibrillation (AF) and heart failure (HF) during medium-term follow-up and there are limited data on the risk analysis of adverse prognosis in this population. In this study, we aimed to evaluate the long-term performance of HBP following AVN ablation in AF and HF. Methods and results Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 19 publications
2
59
0
1
Order By: Relevance
“…What will help these ventricular‐pacing dependant patients with AF and HFrEF? His‐Purkinje system pacing, including His‐bundle pacing (HBP) and left branch bundle pacing (LBBP), were the alternative procedures in patients with indications of bradycardia and heart failure 5–6 . However, very few studies talk about the impact of HBP on these patients compared with BVP.…”
Section: Introductionmentioning
confidence: 99%
“…What will help these ventricular‐pacing dependant patients with AF and HFrEF? His‐Purkinje system pacing, including His‐bundle pacing (HBP) and left branch bundle pacing (LBBP), were the alternative procedures in patients with indications of bradycardia and heart failure 5–6 . However, very few studies talk about the impact of HBP on these patients compared with BVP.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies 4–8 have confirmed the feasibility and efficacy of HPCSP in patients with AF and AVN ablation. These studies demonstrated that permanent HBP with AVN ablation leads to significant improvement in cardiac function in AF patients with narrow QRS who suffered from HF with preserved or reduced ejection fraction.…”
Section: Pacing Strategy In Af and Hfmentioning
confidence: 80%
“…In patients with LBBB undergoing BVP, left ventricular pacing fused with intrinsic ventricular activation have been shown to improve outcomes. But in patients with AF and AVN ablation, this fusion with intrinsic activation is not possible 6 …”
Section: The Impact Of Af On Electrical Synchrony Of Hpcsp and Bvpmentioning
confidence: 99%
“…[ 22 ] In another study of 94 patients undergoing AV node ablation, HBP was successful in 86% of patients with an improvement in LV ejection fraction (from 44.9 ± 14.9% [mean ± standard deviation] at baseline to 57.6 ± 12.5% after a median follow-up of 3.0 years). [ 23 ] The efficacy of HBP may be uncertain in patients with intraventricular conduction delay, significant LV scar and in 10–30% of LBBB patients in whom the site of block may be distal to the HB.…”
Section: Clinical Implications Of His Bundle Pacingmentioning
confidence: 99%